Assessment of the Quality of Education Received by Undergraduate Pharmacy Students in Selected Universities in Nigeria - Okolosi-Patani, Omotejohwo Emily; Adje, Ufuoma David; Arute, John Ejophe; Ahwinawhi, Ufuoma Shalom (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: To assess the self-reported quality of education received by undergraduate pharmacy students and to explore factors influencing career choice. Materials and Methods: A pretested questionnaire was administered to a convenient sample of 2090 pharmacy students in their professional years from selected universities in Nigeria. Respondent’s characteristics and responses were reported as simple proportions and percentages. Results: The response rate was 71%. Only 1028 (69.3%) originally intended to study pharmacy. The desire to provide health care services, 531 (51.7%) and parental pressure 178 (39.0%) were the major motivation for studying pharmacy. More than half, 827 (55.7%) strongly agreed or agreed that the pharmacy training adequately prepared them to practice effectively. However nearly half 740 (49.9%) felt that the pharmacy curriculum was overloaded. Community pharmacy was the most preferred practice area 372 (26.5%) followed by hospital pharmacy practice. Conclusion: Majority of the students considered the quality of undergraduate pharmacy education to be adequate although unnecessarily overloaded. The desire to provide health care services and parental influence were the greatest motivational factors for studying pharmacy. The most preferred area of practice was community pharmacy
Keywords: Undergraduate students; Pharmacy education; Career choices; Nigeria